2016
DOI: 10.1016/j.lfs.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon imaging of endothelin-1-mediated intracellular Ca 2+ handling in smooth muscle cells of rat renal resistance arteries

Abstract: Aims Endothelin-1 (ET-1) is a potent vasoconstrictor which regulates the physiology of cardiorenal system. The aim of this study was to evaluate ET-1-mediated elevation of intracellular Ca2+ in smooth muscle cells (SMC) of renal resistance arteries. Main methods In in vitro studies of primary SMC, which were isolated from rat renal microvessels, the levels of intracellular Ca2+ were calculated from the ratio of emissions at 340 and 380 nm after loading cells with Fura 2-AM dye. In ex vivo studies we used two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…We have shown that ET-1 induces p66Shc Ser36 phosphorylation and mediates protein-protein interactions of p66Shc in renal glomerular cells (7,41,42). Our recent experiments using 2-photon imaging also revealed that treatment of isolated rat renal resistance arteries with ET-1 caused a rapid increase of [Ca 2+ ] i in smooth muscle vasculature of these vessels (43).…”
Section: Discussionmentioning
confidence: 89%
“…We have shown that ET-1 induces p66Shc Ser36 phosphorylation and mediates protein-protein interactions of p66Shc in renal glomerular cells (7,41,42). Our recent experiments using 2-photon imaging also revealed that treatment of isolated rat renal resistance arteries with ET-1 caused a rapid increase of [Ca 2+ ] i in smooth muscle vasculature of these vessels (43).…”
Section: Discussionmentioning
confidence: 89%
“…Ex vivo imaging of [Ca 2+ ] i in SMCs of isolated renal interlobar arteries was carried out as previously described (15). Dissected arteries (150-200 mm inner diameter) were loaded with lowcalcium (0.1 mM Ca 2+ ) physiologic saline solution (PSS) supplemented with 5 mM Fluo-4 AM and 0.05% pluronic acid and stored for 1 h on a rotating shaker at room temperature in the dark.…”
Section: Two-photon Imaging Of [Ca 2+ ] Imentioning
confidence: 99%
“…The isolated intact vascular tree was prepared for 2-photon imaging microscopy as previously described (15). Renal microvessels (diameter, 100-150 mm; identified as interlobular arteries) were loaded with Fluo4 AM calcium indicator to monitor fluctuations in [Ca 2+ ] i .…”
Section: Ca 2+ Oscillations In Smcs Embedded In the Wall Of Renal Resmentioning
confidence: 99%
See 2 more Smart Citations